CIPP evaluation model - The agreement of the five ministers: Arranging and organizing junior high school teachers - Darius Imanuel Wadu; Bambang Ismanto (Graduate School, Universitas Negeri Yogyakarta, 2021)
This study aims to use a descriptive qualitative method to describe the program of the agreement of the five ministers implemented in Salatiga. Based on the findings, the implementation of the program to organize and arrange civil servant teachers in the city of Salatiga is still not going well. This issue prompted additional research into the process of leveling and rearranging teachers. Problems in the implementation of the ongoing program at the Salatiga Education Office were discovered with the assistance of CIPP. In terms of context, the implementation procedures are in line with the regional government’s procedures in terms of vision and mission, objectives, and identification of needs and opportunities. The input is seen to be by the Mayor of Salatiga’s decision, such as aspects of strategy, procedures, and teacher placement. However, the Education, Youth, and Sports Office does not manage funds because there is no allocation. The stages of the process have been running, including readiness identification and monitoring, mutation implementation, and discipline. The result stage demonstrates that while not all of them have achieved their goals, such as equal distribution of teachers in schools, they have done well in terms of benefits, impacts, and sustainability. As a result of the results obtained from the input and output aspects, the Salatiga government must allocate funds for the teacher transfer program for organizing and rearranging middle school teachers in Salatiga to run as expected.